Indices Changes of Central Hemodynamics at Carry Out Anesthesia with Keeping Independent Breathing at Children - Gulchekhra Ashurova1, Nigora Zokirova2, Talat Agzamkhodjayev3, Anvar Yusupov4, Ikhtiyor Mamatqulov5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: The aim of study was to research hemodynamic shifts in conditions of carry out combinedanesthesia on the base of isoflurane with preservation of spontaneous breathing at small surgical operationsin children.Materials and Method: The research was carried out at 44 sick children at the age from 3 to 14 years withinguinal and inguinal hernias (41,7 %), hydrocele was (19,4 %) section of abscesses and suppurations were(38,9%). The duration of anesthesia benefit at 58,3 % patients was from 30 to 40 minutes, at 40,66 % it wasabout 60 minutes.Results: The clinical monitoring was performed with study AP, HR and oxygen. For objective evaluationof cardiovascular functional condition, the echocardiography way was use. The first group patients wereintroduced intravenously the ketamine solution in doze 3 mgr/kg of body weight, propofole in dose 2 mgr/kg of body weight and izoflurane up to 3 ob % in 30-40 minutes after premedication. The second grouppatients were introduced intravenously the ketamine solution in dose 4-5 mgr/body weight and sibazone indose 0,4 mgr/kg.Conclusion: Complex clinical study and taken results of hemodynamic parameters showed the efficiency ofcarried out anesthesia with safety of independent breathing at small surgical operations at children.